Predictors of sickness absence related to musculoskeletal pain: a two-year follow-up study of workers in municipal kitchens - Eija Haukka; Leena Kaila-Kangas; Ritva Luukkonen; Esa-Pekka Takala; Eira Viikari-Juntura; Päivi Leino-Arjas (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVE: We studied predictors of sickness absences (SA) due to musculoskeletal pain over two years among 386 municipal female kitchen workers. METHODS: Pain and SA periods (no/yes) due to pain in seven sites during the past three months were assessed at 3-month intervals over two years by questionnaire. Age, musculoskeletal pain, multisite pain (pain in ≥3 sites), musculoskeletal and other somatic diseases, depressive symptoms, physical and psychosocial workload, body mass index, smoking, and leisure-time physical activity (LTPA) at baseline were considered as predictors. Trajectory analysis and multinomial logistic regression were used. RESULTS: Three trajectories of SA emerged, labelled as "none" (41% of the subjects), "intermediate" (48%), and "high" (11%). With the "none" trajectory (no SA) as reference, pain in all musculoskeletal sites excepting the low back predicted belonging to the "intermediate" [odds ratio (OR) 1.82-2.48] or "high" (OR 2.56-3.74) trajectory adjusted for age; multisite pain predicted membership of the "intermediate" [OR 2.15, 95% confidence interval (95% CI) 1.38-3.34] or "high" (OR 4.66, 95% CI 2.10-10.3) trajectories. In a mutually adjusted final model, smoking (OR 2.12, 95% CI 1.22-3.69), multisite pain (OR 1.87, 95% CI 1.15-3.02), and overweight/obesity (OR 1.71, 95% CI 1.08-2.72) predicted belonging to the "intermediate" trajectory, while depressive symptoms (OR 3.57, 95% CI 1.57-8.10), musculoskeletal diseases (OR 3.18, 95% CI 1.37-7.37), and multisite pain (OR 2.72, 95% CI 1.15-6.40) were associated with the "high" trajectory. CONCLUSION: Along with the number of pain sites and musculoskeletal diseases, attention to depressive symptoms, smoking, and overweight/obesity is needed to tackle SA related to musculoskeletal pain.